Dilemma of Epigenetic Changes Causing or Reducing Metabolic Disorders in Offsprings of Obese Mothers - Sharma, Shikha; Bhonde, Ramesh (Hormone and Metabolic Research, 2023)
Maternal obesity is associated with fetal complications predisposing later to the development of metabolic syndrome during childhood and adult stages. High-fat diet seems to influence individuals and their subsequent generations in mediating weight gain, insulin resistance, obesity, high cholesterol, diabetes, and cardiovascular disorder. Research evidence strongly suggests that epigenetic alteration is the major contributor to the development of metabolic syndrome through DNA methylation, histone modifications, and microRNA expression. In this review, we have discussed the outcome of recent studies on the adverse and beneficial effects of nutrients and vitamins through epigenetics during pregnancy. We have further discussed about the miRNAs altered during maternal obesity. Identification of new epigenetic modifiers such as mesenchymal stem cells condition media (MSCs-CM)/exosomes for accelerating the reversal of epigenetic abnormalities for the development of new treatments is yet another aspect of the present review.
Keywords: maternal obesity; MSCs secretome; epigenetic modification; epigenetic modifier; nutrition, metabolic syndrome